Framing economic news: an examination of coverage of the Growth, Employment and Redistribution (GEAR) strategy in Business Day - Mudzamiri, Wonder Tariro (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2009)
This thesis examines the way in which Business Day portrayed the neo-liberal logic of the Growth, Employment and Redistribution (GEAR) strategy as both common sense and natural. It utilises framing analysis, adapting its application to the context of media studies as the guiding theoretical framework in trying to understand how Business Day, as representative of the mainstream financial media, frame economic policy issues. Using content analysis, the thesis examines how elite sources are the preferred news sources above ordinary citizens and are thus in a position to shape news content in line with their neo-liberal views on the economy. The thesis analyses how Business Day, by means of the globalisation frame and other frames, legitimated and in the process perpetuated the GEAR strategy as the macroeconomic policy of choice for South Africa in 1996 against the background of the country's political transformation and economic policy development in preceding years.
Keywords: Business day; English newspapers -- South Africa; South African newspapers; Mass media -- Economic aspects; Economic development -- South Africa; South Africa -- Economic policy; South Africa -- Politics and government -- 1994-